Foreign Direct Investment and Employment in Agricultural Sector in Nigeria - Sokunbi, Gbenro Matthew; Johson, Adebayo Akanbi; Atanda, Olatunde Olaide; Aderemi, Timothy Ayomitunde (The Journal of Accounting and Management, 2023)
The agricultural sector in Nigeria holds substantial prominence within the broader framework of the nation's economy. Throughout the years, the agricultural sector has experienced limited growth potentials due to inadequate financial support allocated to the industry. The insufficient funding of the agricultural sector can be attributed to the government and financial institutions' apparent neglect of the sector. As such, exploring FDI for agricultural job creation in Nigeria becomes inevitable. Therefore, the study employed DOLS to assess nexus between FDI and employment in agricultural sector in Nigeria from 1990 to 2021. The findings from the study are summarized as follows; both agricultural gross production (AGP) and government expenditure on agriculture (GEA) contribute a significant negative impact on employment in agricultural sector in Nigeria. Meanwhile, FDI contributes an insignificant impact on employment generation in agriculture in Nigeria. Against these findings, the study makes the following recommendations; the Nigerian policymakers should establish a conducive and supportive ecosystem that can effectively facilitate the expansion prospects and influx of foreign investments in the agricultural industry. So that the prevailing agricultural landscape would possess the necessary attributes to foster and stimulate international investment. Also, it is imperative for the Nigerian policymakers to prioritise the expansion of the agricultural sector by augmenting the allocation of funds from the national budget towards this crucial domain.